Pre-registration and pre-analysis plans in experimental economics - Taisuke Imai; Severine Toussaert; Aurélien Baillon; Anna Dreber; Seda Ertac; Magnus Johannesson; Levent Neyse; Marie-Claire Villeval (Osaka University, Institute of Social and Economic Research (ISER), 2025)
The open science movement has gained significant momentum over the past decade, with pre-registration and the use of pre-analysis plans being central to ongoing debates. Combining observational evidence on trends in adoption with survey data from 519 researchers, this study examines the adoption of pre-registration (potentially but not necessarily including pre-analysis plans) in experimental economics. Pooling statistics from 19 leading journals published between 2017 and 2023, we observe that the number of papers containing a pre-registration grew from seven per year to 190 per year. Our findings indicate that pre-registration has now become mainstream in experimental economics, with two-thirds of respondents expressing favorable views and 86% having pre-registered at least one study. However, opinions are divided on the scope and comprehensiveness of pre-registration, highlighting the need for clearer guidelines. Researchers assign a credibility premium to pre-registered tests, although the exact channels remain to be understood. Our results suggest growing support for open science practices among experimental economists, with demand for professional associations to guide researchers and reviewers on best practices for pre-registration and other open science initiatives.
Keywords: A14; C12; C18; C80; C90; I23; 330; pre-registration; pre-analysis plans; experimental economics; open science